PEDAGOGICAL TOOLS FOR DEVELOPING IMPROVISATION ABILITY OF FUTURE PRIMARY CLASS TEACHERS - Kuralbayeva Aliya; Adilova Munisa Furqatovna; Tursunova Malika Baxtiyor kizi; Kasimova Odina Alimjanovna (The Bioscan, 2025)
This article talks about the competence of pedagogical improvisation, the importance of pedagogical improvisation in the educational system, ways to implement improvisation in the work of a future primary school teacher. In accordance with the main components of the educational process in changing conditions of pedagogical activity, pedagogical improvisation is a process aimed at clarifying the goals of a particular lesson, the content of the educational material, methodological perception and communication in accordance with the goal, and the naming of pedagogical improvisation in dictionaries is also described. The improvisational nature of pedagogical activity creates the necessary conditions for the satisfaction of the teacher's moral and psychological needs for success, professional and personal growth, which is measured by both career growth and the rise to the highest level of mastery and wisdom. The possibilities of various actions for teachers in the process of improvisation are highlighted, and the criteria for pedagogical improvisation are highlighted. In pedagogical improvisation, the components of the creative dominant are attention, imagination, and inspiration. We briefly touched upon the characteristics of pedagogical improvisation as a component of pedagogical creativity.